2018
DOI: 10.1007/s10902-018-9995-x
|View full text |Cite
|
Sign up to set email alerts
|

Buffering Effects for Negative Life Events: The Role of Material, Social, Religious and Personal Resources

Abstract: The changes in subjective wellbeing experienced following negative life events can be buffered by various types of resources. In the present article, we compare the influences of material, religious, social and personality resources using the Swiss Household Panel (SHP) in a unified framework. Fixed effects regression models are estimated for four negative life events: separation, death of a closely related person, unemployment and disability. Buffering effects are estimated by interacting time since the event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 52 publications
2
13
5
1
Order By: Relevance
“…This finding is inconsistent with the findings of who reported a negative association between social support and response to widowhood. It is also inconsistent with the findings of Kuhn and Brulé (2019) who reported that emotional support and frequency of contact with friends reinforce the negative effects after the loss of a loved one. These inconsistent findings raise the need for further research in this area.…”
Section: Discussioncontrasting
confidence: 98%
See 3 more Smart Citations
“…This finding is inconsistent with the findings of who reported a negative association between social support and response to widowhood. It is also inconsistent with the findings of Kuhn and Brulé (2019) who reported that emotional support and frequency of contact with friends reinforce the negative effects after the loss of a loved one. These inconsistent findings raise the need for further research in this area.…”
Section: Discussioncontrasting
confidence: 98%
“…A recent study that examined the roles of material, social, religious, and personal factors as a buffer against the impact of negative life events, including the death of a loved one (Kuhn & Brulé, 2019). Material resources were not buffering effects for negative life events.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…In contrast, analysis of Swiss panel data found that neither income nor wealth buffered the effects of disability acquisition, however 'internal' resources (personal spirituality and personality attributes) did show buffering effects. 30 Although there is substantial evidence concerning associations between disability and increased risk of exposure to well-established social determinants of poor health, 31 relatively few studies have investigated the effects of such exposure on the PWB of people with disability. Further, many of the studies that explore factors that mediate the relationship between disability and PWB focus on younger or older age groups.…”
Section: Introductionmentioning
confidence: 99%